length of AB is
.
Explanation:
Here we have , two points as A(3,- 4, 2) and B(2, -1, 3) . We need to find the length of AB. Let's find out:
We know that , Distance between any two points
is given by distance formula as :
![Distance = √((x_2-x_1)^2+(y_2-y_1)^2+(z_2-z_1)^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s0iure9mi70ksqqpia4hzd9kihn29peq6c.png)
Putting A(3,- 4, 2) and B(2, -1, 3) in above formula :
⇒
![Distance = √((x_2-x_1)^2+(y_2-y_1)^2+(z_2-z_1)^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/s0iure9mi70ksqqpia4hzd9kihn29peq6c.png)
⇒
![Distance = √((2-3)^2+((-1)-(-4))^2+(3-2)^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rw1yyezs0072awoa5i98yrw4jop5ppcngl.png)
⇒
![Distance = √(1+9+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/q97w4kkk6cyrea5codzwbddukzcud57eih.png)
⇒
![Distance = √(11)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bgp5zjvqrlby2d8xoj3s5e4rdz7c95eflk.png)
Therefore , length of AB is
.